Peppermint extract improves egg production and quality, increases antioxidant capacity, and alters cecal microbiota in late-phase laying hens - Bai, Miaomiao; Liu, Hongnan; Zhang, Yihui; Wang, Shanshan; Shao, Yirui; Xiong, Xia; Hu, Xin; Yu, Rongyao; Lan, Wei; Cui, Yadong; Kong, Xiangfeng (Frontiers in Microbiology, 2023)
Introduction Peppermint contains substantial bioactive ingredients belonging to the phytoestrogens, and its effects on the production of late-laying hens deserve more attention. This study evaluated the effects of dietary peppermint extract (PE) supplementation on egg production and quality, yolk fatty acid composition, antioxidant capacity, and cecal microbiota in late-phase laying hens. Method PE powder was identified by UPLC-MS/MS analysis. Two hundred and sixteen laying hens (60 weeks old) were randomly assigned to four treatments, each for 28 days: (i) basal diet (control group, CON); (ii) basal diet + 0.1% PE; (iii) basal diet + 0.2% PE; and (iv) basal diet + 0.4% PE. Egg, serum, and cecal samples were collected for analysis. Results Dietary PE supplementation increased the laying rate, serum triglyceride, immunoglobulin G, and total antioxidant capacity, while 0.2 and 0.4% PE supplementation increased eggshell thickness, serum total protein level, and superoxide dismutase activity of laying hens compared with the CON group (P < 0.05). PE addition in diets increased the C14:0, C18:3n3, C18:3n6, C23:0, C24:0, and C24:1n9 contents in the yolk. In addition, the egg yolk saturated fatty acid content was higher (P < 0.05) in the 0.2 and 0.4% PE groups compared with the CON and 0.1% PE groups. The microbiota analysis revealed that the cecal phylum Proteobacteria was decreased (P < 0.05) in the PE-supplemented groups. A total of 0.4% PE supplementation increased the cecal richness of gram-positive bacteria and decreased the richness of gram-negative and potentially pathogenic bacteria compared with the 0.1% PE group (P < 0.05). Microbial function prediction analysis showed that the cecal microbiota of the PE group was mainly enriched by fatty acid degradation, fatty acid metabolism, amino sugar metabolism, nucleotide sugar metabolism, and other pathways. Regression analysis suggested that 0.28–0.36% PE supplementation was the optimal level for improving egg production and quality, antioxidant capacity, and yolk fatty acid in late-phase laying hens. Discussion Dietary PE supplementation improved egg production and quality (including yolk fatty acid composition) by increasing serum IgG and antioxidant capacity and modulating the intestinal microbiota in late-phase laying hens.